Quantum Correlations and Quantum Non-Locality: A Review and a Few New Ideas - Genovese, Marco; Gramegna, Marco (Applied sciences, 2019)
In this paper we make an extensive description of quantum non-locality, one of the most intriguing and fascinating facets of quantum mechanics. After a general presentation of several studies on this subject dealing with different but connected facets of quantum non-locality, we consider if this, and the friction it carries with special relativity, can eventually find a “solution” by considering higher dimensional spaces.